2019
DOI: 10.14309/ajg.0000000000000493
|View full text |Cite
|
Sign up to set email alerts
|

Mongersen (GED-0301) for Active Crohn's Disease: Results of a Phase 3 Study

Abstract: Introduction: The objective was to assess the efficacy and safety of GED-0301, an antisense oligodeoxynucleotide to Smad7, in active Crohn's disease (CD). METHODS: This phase 3, blinded study randomized patients (1:1:1:1) to placebo or 1 of 3 once-daily oral GED-0301 regimens: 160 mg for 12 weeks followed by 40 mg continuously or alternating placebo with 40 or 160 mg every 4 weeks through week 52. RESULTS: I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(43 citation statements)
references
References 6 publications
1
35
0
Order By: Relevance
“…The complexity of targeted ASO is depicted by mongersen, an orally administered ASO against Smad7 aimed to restore transforming growth factor-beta (TGF-β) signaling. The phase II clinical trial results [ 88 ] were encouraging whereas the phase III clinical trial showed no significant efficacy [ 89 ]. The investigators stated that no mucosal drug concentrations were measured during the phase III trial, which may have partly explained the observed ineffectiveness.…”
Section: Preclinical Studies On Local Tnf-α Inhibitionmentioning
confidence: 99%
“…The complexity of targeted ASO is depicted by mongersen, an orally administered ASO against Smad7 aimed to restore transforming growth factor-beta (TGF-β) signaling. The phase II clinical trial results [ 88 ] were encouraging whereas the phase III clinical trial showed no significant efficacy [ 89 ]. The investigators stated that no mucosal drug concentrations were measured during the phase III trial, which may have partly explained the observed ineffectiveness.…”
Section: Preclinical Studies On Local Tnf-α Inhibitionmentioning
confidence: 99%
“…Following the encouraging results of a placebo-controlled phase 2 trial of Mongersen showing a 55%–65% clinical remission rate at the highest doses of the drug [ 11 ], a phase 3 randomized double-blind, placebo-controlled, multicentre study was terminated early by the data monitoring committee as a consequence of a lack of efficacy [ 12 ]. Factors accounting for such a huge disparity between these trials remain unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Consistently, a phase 1 study conducted showed that oral administration a Smad7 AS-containing oral drug, denominated Mongersen (previously termed GED-0301) in active CD patients was safe and associated with clinical benefit, and later on, two distinct phase 2 studies confirmed the safety of the drug and showed that Mongersen induced clinical and endoscopic improvement in steroid-dependent and/or resistant CD patients [ 9 , 10 , 11 ]. Despite these positive results, a recent phase 3 study was discontinued due to an interim analysis that documented the apparent clinical inefficacy of the drug [ 12 ]. The reasons for the discrepancy between the phase 3 study and the previous clinical trials remain to be ascertained even if differences in the patient criteria selection may have contributed.…”
Section: Introductionmentioning
confidence: 99%
“…Mongersen is an oral drug, formulated for preferential release in the terminal ileum and right-sided colon for optimal treatment of CD [87, 88]. However, even though phase II studies showed high rates of clinical remission (65 vs. 10% with placebo) [89, 90], a recent large-scale phase III study was stopped due to lack of efficacy, and it remains unclear whether mongersen will ever be applied clinically [91].…”
Section: Inhibition Of Cytokine Pathwaysmentioning
confidence: 99%